ANALISIS DAN DESAIN SISTEM PEMBUMIAN GARDU DISTRIBUSI PADA LAHAN SEMPIT DI TANAH BERBATU - I W. A. Premei Artha; I G.N. Janardana; I W. Arta Wijaya (Jurnal SPEKTRUM, 2021)
A disturbance in the groundhing system is caused by a disturbance current which isflowed to the ground which will cause a difference in tension on the ground surface dueto high ground resistance. On rocky soils with ground resistance in excess of 200 ?-meters it is very difficult to determine a suitable grounding system. The purpose of thisresearch is to analyze the design of an appropriate earthing system on narrow land onrocky ground which will be used as a reference for selecting the grounding system at atKampus Unud Jimbaran feeders. The method used is to take measurements on rockysoil then measure and determine the proper earthing design to use. The optimal resultsobtained for the grounding system on narrow land on rocky soil is a grid groundingsystem because it produces the lowest earthing resistance value in dry soil conditionsand wet soil conditions, namely 0.6269 ohms on dry soil and 0.4314 ohms on wet soil. has met the standard according to IEEE std 80-2013, which is <1 ohm with 16x16 rodsin an area of 4 m2.